Radiographic Evaluation of Acetabular Fractures: Review and Update on Methodology. Issue 3 (1st February 2018) - Mauffrey, Cyril; Stacey, Stephen; York, Philip J.; Ziran, Bruce H.; Archdeacon, Michael T.
Abstract : Despite increased availability of modern imaging techniques, plain radiographs remain the initial step in the classification of acetabular fractures. The ability to interpret the injury configuration allows the surgeon to develop a thorough preoperative plan and to evaluate the quality of reduction and fixation intraoperatively. Proficiency in the mental conversion of a two-dimensional radiograph into a three-dimensional conceptual image is imperative. The widely used radiographic classification scheme developed by Judet and Letournel in the 1960s is both practical and simple. However, understanding the subtleties of the fracture pattern can be a challenge even for experienced surgeons. Current evaluation methods include CT and three-dimensional reconstructions in addition to plain radiographs. Our diagnostic algorithm uses three plain radiographs to classify the fracture into one of the 10 fracture patterns described by Judet and Letournel.